Multiple scattering of charged particles in a free electron gas - Archubi, Claudio Darío (2006)
We study the influence of electron-scattering processes on the angular distributions of point particles moving through a free-electron gas. Previous calculations for slow ions are extended to all (nonrelativistic) velocities. The formulation is based on the extension of the multiple-scattering theory to the case of particles moving through a free-electron gas, using Lindhard’s dielectric function to separately evaluate the contributions of binary (electron-hole) and collective (plasmon) excitations. We find that the angular spread of the beam of particles is dominated by binary collisions. The results for the width of the angular distribution are compared with an integral expression derived by Lindhard.